Mitochondrial calcium signaling and redox homeostasis in cardiac health and disease - Popoiu, Tudor-Alexandru; Maack, Christoph; Bertero, Edoardo (Frontiers in Molecular Medicine, 2023)
The energy demand of cardiomyocytes changes continuously in response to variations in cardiac workload. Cardiac excitation-contraction coupling is fueled primarily by adenosine triphosphate (ATP) production by oxidative phosphorylation in mitochondria. The rate of mitochondrial oxidative metabolism is matched to the rate of ATP consumption in the cytosol by the parallel activation of oxidative phosphorylation by calcium (Ca 2+ ) and adenosine diphosphate (ADP). During cardiac workload transitions, Ca 2+ accumulates in the mitochondrial matrix, where it stimulates the activity of the tricarboxylic acid cycle. In this review, we describe how mitochondria internalize and extrude Ca 2+ , the relevance of this process for ATP production and redox homeostasis in the healthy heart, and how derangements in ion handling cause mitochondrial and cardiomyocyte dysfunction in heart failure.